Changes Induced by Elk Browsing in the Aboveground Biomass Production and Distribution of Willow (Salix monticola Bebb): Their Relationships with Plant Water, Carbon, and Nitrogen Dynamics - H. Raul Peinetti; Romulo S. C. Menezes; Coughenour, Michael B. (Oecologia, 2001)
Willows are dominant woody plants of many high-elevation riparian areas of the western USA, and constitute an important food resource for various ungulates, which tend to concentrate in riparian areas. The response of willow to browsing was analyzed in the elk winter range of Rocky Mountain National Park, by considering the effect of elk browsing on Salix monticola Bebb, one of the most common willow species in this area. Unbrowsed and browsed treatments were established during the 1997 growing season (May to October), using eight long-term exclosures built in the fall of 1994. Plants in the browsed treatment were in the areas open to browsing, but they were protected from browsing by small exclosures during the experimental period. Winter browsing by elk induced the following measured responses in plant morphology and development: (1) higher shoot biomass production but similar leaf biomass and leaf area per plant, (2) a lower number of and bigger shoots, (3) a lower number of and bigger leaves, and (4) flower inhibition. In addition, we infer that browsing induces (5) lower belowground allocation and (6) a more negative N balance but a higher soil N uptake. We conclude that elk browsing negatively affects willow even though willow compensate for aboveground biomass removal. Continuous browsing produces long-term changes in willow morphology which constrain plant growth and development. High browsing utilization, as occurred in this experiment, could therefore reduce the competitive ability and survivorship of willow, in particular under drier environmental conditions.